MHD flow over exponential radiating stretching sheet using homotopy analysis method - Mabood, Fazle; Khan, W.A.; Md. Ismail, A.I. (Elsevier, 2017)
An analytical solution for MHD boundary layer flow of a viscous incompressible fluid over an exponentially stretching sheet is developed in this study. The effect of thermal radiation is included in the energy equation. Through suitable similarity transformations, the governing equations are transformed into a system of nonlinear ordinary differential equations. Homotopy analysis method (HAM) has been used to get accurate and complete analytic solution. This study reveals that the governing parameters, namely, the magnetic and the radiation parameters have major effects on the flow field, skin friction coefficient, and the heat transfer rate. The magnetic field enhances the dimensionless temperature inside the thermal boundary layer whereas reduces the dimensionless velocity inside the hydrodynamic boundary layer. Heat transfer rate becomes low with magnetic and radiation parameters while the friction factor is increased with magnetic field. Moreover, a comparative study between the previously published and the present results in special cases is conducted and an excellent agreement is found between them.